Romania Financial Sector Assessment - World Bank; International Monetary Fund (World Bank, Washington, DC, 2018)
Romania’s financial sector has strengthened significantly over the last few years. Effective supervisory measures have helped reduce the high level of non-performing loans (NPLs) from 21.5 percent at its peak in 2013 to 6.4 percent as of December 2017.However, some vulnerabilities are emerging. Banks’ holdings of domestic sovereign paper have grown large, exposing them to valuation losses in case of an increase in interest rates or sovereign risk spreads. Banks’ indirect exposures to government guarantees through the Prima Casa program further strengthens the sovereign-bank nexus. An increase in interest rates may also negatively impact NPL ratios on banks’ mortgage portfolios, which are growing fast and are at variable rates. The share of foreign exchange (FX) denominated loans and deposits significantly decreased, but remains relatively high, and a large share of corporate borrowers is unhedged. Finally, lending practices of non-bank financial lenders (NBFLs) may lead to loan defaults and reputational risks for the banking sector. As the financial system is small, shocks may further discourage financial intermediation, which is already among the lowest in the European Union (EU). The NBR is transitioning to a risk-based supervisory approach that needs further enhancements. The new Supervisory Review and Evaluation Process (SREP) Guidelines of the European Banking Authority (EBA) are still in the initial stages of implementation. The NBR should conduct more risk-focused, banking industry-wide thematic analyses and develop its off-site monitoring tools, such as by conducting bottom up stress tests.Financial intermediation relative to the economy is low and declining.On the demand side, credit needs remain, overall, limited due to low enterprise density, poor health of the enterprise sector, and high number of foreign owned firms (compared to peers). The economic growth had a positive spillover in the enterprise sector, but this did not translate into increased investment activity, despite an unprecedented low interest rate environment. On the supply side, the supply of credit has been constrained by several factors including: i) an acute deterioration of asset quality, particularly among MSMEs, after the crisis, ii) banks’ deleveraging pressures, iii) deficiencies in the credit enabling infrastructures (credit reporting, insolvency), iv) preference of banks for sovereign debt, as well as government guaranteed debt in a context of fiscal expansion, v) lack of depth in the NBFI segment, and vi) declining use of public partial credit guarantees due to operational problems. As a result, access to credit is particularly problematic for certain firm segments that are underserved by the banking sector, including for micro, small and medium-sized enterprises (MSMEs), start-ups, the agriculture sector, and in rural areas.Improving financial inclusion may require broader solutions including i) a better use of the Posta Romana network of branches, ii) measures to enable credit unions to expand and offer more financial services while strengthening supervision, iii) the adoption of incentive mechanisms to accelerate the expansion of digital finance solutions, and iv) the promotion of financial inclusion and literacy as well as effective consumer protection mechanisms.